PTU-068 Outcomes of disease modifying therapy delivered to crohn's disease patients following intestinal resection. (22nd June 2015) - O'connor, A; Taylor, J; Rabb, N; Gracie, D; Leigh, K; Scott, N; Ford, AC; Hamlin, PJ
Abstract : Introduction: Follow-up of patients resected for Crohn's disease (CD) have shown that in the absence of treatment, the post-operative recurrence rate is 70–90% within one year of the operation and 83–100% within 3 years. Prophylactic medication and disease monitoring has been proven to decrease the rate of clinical and endoscopic recurrence. Method: We aimed to examine current practices in our large tertiary referral centre on postoperative prescriptions of disease modifying therapy for CD. We performed a retrospective analysis by interrogating the pathology database over a five year period from 2009 to 2013 to identify cases and data was extracted by chart review. Results: 152 resections were identified. 106 patients had been given disease-modifying therapy. 3 patients were involved in a drug trial and were excluded. 66.3% of patients had therapy commenced before the first followup colonoscopy or imaging had been performed. As first-line 79 patients had thiopurine monotherapy (64 azathioprine, 14 mercaptopurine, 1 tacrolimus). 11 patients had anti-tnf monotherapy (8 adalimumab, 2 infliximab, 1 certolizumab). 13 had combination therapy with an immunomodulator and an anti-tnf. The outcomes are outlined in Table 1 . Conclusion: While there is no clear benefit observed for drug therapy over no drug therapy, it is likely that those who receive no treatment have a selection bias of clinically silent disease or negative initial followup investigations. Among those in whom disease-modifying therapy is prescribed there is a trend for those on combination therapy to have a better clinical response as well as steroid free, repeat-resection free survival at end of followup. Disclosure of interest: None Declared.